KUPU-KUPU DALAM KARYA TAPESTRI - YULI PUTRIANI, Drs. Erwin A, M.Sn., Dra. Minarsih, M.Sn. (Serupa The Journal of Art Education, 2016)
Butterfly has special attraction. It has beautiful shape wings, color pattern and also it has interesting body movement. Characteristics of these butterflies can be used as guidance in revealing the inner situation a bout the issue of life. This thesis used a combination of several techniques Rata, Klim, Soumak, and Giordes, coil and embroidery tapestry techniques. By combining several techniques, it can show a new creation. Visual elements and principles of art concerned in the realization of the creation in order to be looks interesting. There are several titles of butterfly creations that the writer made, including: Basilarchia Achippus, Papiliondea, Papilio Maackii, Crimson Rose, Danaus plexippus, pipevine Blue, Swallowtail.keywords: Kupu-kupu, Tapestri, Koil dan Sulam